BEAM study (Breathing, Education, Awareness, Movement): a randomised controlled feasibility trial of tai chi exercise in patients with COPD. Issue 1 (20th November 2020) - Yeh, Gloria Y.; Litrownik, Daniel; Wayne, Peter M.; Beach, Douglas; Klings, Elizabeth S.; Reyes Nieva, Harry; Pinheiro, Adlin; Davis, Roger B.; Moy, Marilyn L.
Abstract : Background: Despite therapeutic advances, the management of chronic obstructive pulmonary disease (COPD) remains complex. There is growing interest in multidimensional, mind-body exercises to improve both physical and psychosocial aspects of COPD burden. Few US data are available in this population on tai chi (TC) a mind-body exercise incorporating physical activity, breathing and mindful awareness. We explored feasibility and preliminary efficacy of TC in COPD in an US academic medical setting. Methods: Patients with COPD Global Obstructive Lung Disease (GOLD) stages 2–4 were randomised to a 12-week TC programme or education control. At 12 weeks, those in TC were randomised again to continue in maintenance classes or not to further explore optimal duration. All groups were followed to 24 weeks. Feasibility/safety parameters were analysed descriptively. Preliminary between-group differences were estimated in symptoms (dyspnoea, fatigue), health-related quality-of-life (Chronic Respiratory Questionnaire CRQ), cognitive-emotional measures (mood, COPD self-efficacy) and functional status (6 min walk test, lower body strength, flexibility, physical activity). Results: Ninety-two subjects were randomised (N=61 TC, N=31 education). Mean age was 68±8 years, 66% male, mean forced expiratory volume in 1 s % predicted 57±13, 28% were GOLD stage 3–4. Overall retention was 85%. Nineteen adverse events occurred, most being study-unrelated COPD exacerbations. From baseline to 12 weeks, there were between-group improvements favouring TC, in CRQ-total (Cohen's d effect size (ES)=0.46; adj mean diff (AMD)=0.31), CRQ-emotion (ES=0.54; AMD=0.49), Centre for Epidemiologic Studies Depression (ES=−0.37; AMD=2.39) and Patient-Reported Outcome Measurement Information System (PROMIS)-fatigue (ES=−0.34; AMD=−0.17). From baseline to 24 weeks, there was an improvement favouring TC in CRQ-dyspnoea (ES=0.41; AMD=0.46). Among TC participants, there was a positive effect of maintenance classes on self-efficacy (ES=−0.69; AMD=−0.40), 6 min walk (ES=0.56; AMD=49.26 feet), PROMIS-fatigue (ES=−0.41; AMD=−0.28) and chair stand (0.43; AMD=0.56). Conclusion: TC in patients with COPD is feasible and safe. Preliminary analyses support a potential modest role in improving quality-of-life, cognitive-emotional health and function that should be further studied. Trial registration number: NCT01551953 . IRB reference: BIDMC 2010P-000412; VA 2540.